Features of near and far scrape-off layer heat fluxes on the Wendelstein 7-X inboard limiters. (5th November 2019) - Niemann, H.; Jakubowski, M.W.; Effenberg, F.; Bozhenkov, S.A.; Cannas, B.; Carralero, D.; Langenberg, A.; Pisano, F.; Rahbarnia, K.; Rudischhauser, L.; Stange, T.; Warmer, F.; et al.
Abstract: The power fall-off length is used as a characteristic dimension to describe the power exhaust in the scrape-off layer (SOL) in magnetic confinement fusion devices. Measurements from the limiter campaign of the stellarator Wendelstein 7-X with inboard limiters are presented with the first-time characterization of the limiter heat loads. Two fall-off regimes are found with a narrow near SOL with power fall-off length in millimeters and a wider far SOL with fall-off lengths of several centimeters. An attempt is made to describe both regimes with a scaling law for plasma with different heating powers and densities. The results confirm the major geometry effects of the connection length on the heat transport predicted by 3D modeling.